2014
DOI: 10.1007/s10886-014-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific Volatile Compounds from Mango Elicit Oviposition in Gravid Bactrocera dorsalis Females

Abstract: Selecting a suitable oviposition site is crucial to the fitness of female insects because it determines the successful development of their offspring. During the oviposition process, an insect must use cues from the external environment to make an appropriate choice of where to lay eggs. Generalist insects can detect and react to a plethora of cues, but are under selection pressure to adopt the most reliable ones to override noise and increase efficiency in finding hosts. The oriental fruit fly, Bactrocera dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…In C . capitata , for instance, studies revealed that sexually mature virgin females are attracted to the odor of male-produced pheromone, while mated females are more interested in finding suitable oviposition sites and are therefore more attracted to the odor of host fruits 4245 . Considering these findings, we suggest that OBP genes up-regulated in virgins, in comparison with immature flies, may be involved in pheromone perception.…”
Section: Resultsmentioning
confidence: 99%
“…In C . capitata , for instance, studies revealed that sexually mature virgin females are attracted to the odor of male-produced pheromone, while mated females are more interested in finding suitable oviposition sites and are therefore more attracted to the odor of host fruits 4245 . Considering these findings, we suggest that OBP genes up-regulated in virgins, in comparison with immature flies, may be involved in pheromone perception.…”
Section: Resultsmentioning
confidence: 99%
“…First mentioned as a potential oviposition cue for Ae. aegypti 50 and later for T. amboinensis 51, it has also been implicated as an oviposition cue in other dipterans including the oriental fruit fly, Bactrocera dorsalis 52 and the bean seed fly, Delia platura 53. It therefore appears that octenol detection may be an ancestral cue in insects and an oviposition cue in Dipterans53.…”
Section: Discussionmentioning
confidence: 99%
“…dorsalis exhibits sexually dimorphic behavior, which is influenced by olfactory cues expressed during specific developmental stages [19,20,21]. When the male flies reach sexual maturity, they are strongly attracted to and compulsively feed on Methyl eugenol (ME) (non-host compounds), and this behavior is used to control B .…”
Section: Introductionmentioning
confidence: 99%